2019
DOI: 10.1039/c9ra07069a
|View full text |Cite
|
Sign up to set email alerts
|

Fe2+ doped in CsPbCl3 perovskite nanocrystals: impact on the luminescence and magnetic properties

Abstract: The CsPb1−xFexCl3 NCs were synthesized and an appropriate amount of Fe2+ doping can enhance PLQY and average PL lifetimes. Meanwhile, an obvious hysteresis behavior has been observed for the NCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
(41 reference statements)
8
33
0
Order By: Relevance
“…The degree of acidity and basicity of the ligands is also important for effective passivation, as the defects can have a varying degree of acidity or basicity. Over the years, a wide range of organic acids and amines ( e.g ., oleylamine/oleic acid, octylamine, phosphonic acids (PAs), APTES, l -cysteine, aniline/benzylamine, phenethylamine, and n -trioctylphosphine (TOP) have been tested as ligands for LHP NCs. ,,,, For instance, in the case of CsPbI 3 , Cs + is considered as a weak acid, Pb 2+ a weak acid, as well, and I – a weak base, while in the case of MAPbBr 3 , MA + is a weak acid and Br – is a weak base (though stronger than I – ) . Based on the Pearson acid/base case concept, weak acid defects require weak base ligands, while weak base defects require weak acid ligand for optimal passivation .…”
Section: Surface Chemistry Of Colloidal Halide Perovskite Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of acidity and basicity of the ligands is also important for effective passivation, as the defects can have a varying degree of acidity or basicity. Over the years, a wide range of organic acids and amines ( e.g ., oleylamine/oleic acid, octylamine, phosphonic acids (PAs), APTES, l -cysteine, aniline/benzylamine, phenethylamine, and n -trioctylphosphine (TOP) have been tested as ligands for LHP NCs. ,,,, For instance, in the case of CsPbI 3 , Cs + is considered as a weak acid, Pb 2+ a weak acid, as well, and I – a weak base, while in the case of MAPbBr 3 , MA + is a weak acid and Br – is a weak base (though stronger than I – ) . Based on the Pearson acid/base case concept, weak acid defects require weak base ligands, while weak base defects require weak acid ligand for optimal passivation .…”
Section: Surface Chemistry Of Colloidal Halide Perovskite Ncsmentioning
confidence: 99%
“…For example, butylphosphonic acid 4-ammonium chloride with a combination of phosphate and amino functional groups can simultaneously passivate MA + , Pb 2+ , and I – defects . Additionally, suaraine, polyaniline, and quaternary ammonium salts have been shown to be good capping ligands for MAPbI 3 bulk, MAPbI 3 film, and MAPbBr 3 bulk, respectively. , Peptides containing both −NH 3 + – and −COO – – in one molecule have been used to passivate MA + , Pb 2+ , and Br – of MAPbBr 3 perovskite NCs . Similarly, trifunctional l -cysteine has been used to passivate MAPbBr 3 perovskite NCs and induced self-assembly of perovskite NCs, based on synergistic effects among −NH 3 + –, −COO – –, and −SH– groups .…”
Section: Surface Chemistry Of Colloidal Halide Perovskite Ncsmentioning
confidence: 99%
“…As shown in the XRD pattern spectra (Figure S9a,b, Supporting Information), Fe 3+ , Al 3+ , and Sb 3+ could also substitute Pb 2+ sites because of the smaller ionic radii of Fe 3+ , Al 3+ , and Sb 3+ ions relative to Pb 2+ ions. [53][54][55][56][57][58] However, the measured PLQYs of Al 3+ -10%, Fe 3+ -10%, and Sb 3+ -10% PeQDs under the same experimental conditions are 37.96%, 35.26%, and 85.18%, respectively, which are obviously lower than that of 10% In 3+ -doped CsPbBr x I 3−x PeQDs (Figure S9c,d, Supporting Information). The stability of M 3+ (M 3+ = Fe 3+ , Al 3+ , and Sb 3+ )-doped CsPbBr x I 3−x PeQDs in n-hexane only remains for ≈10 days in atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…As two stable oxidation states of iron, Fe 2+ and Fe 3+ have recently been doped in CsPbCl 3 NCs. [35][36][37] Hu et al prepared Fe 2+ doped CsPbCl 3 NCs, which exhibited the highest PLQY of 6.2%. 35 Shyamal et al doped Fe 2+ in CsPbBr 3 NCs for use as an efficient photocatalyst for the reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Hu et al prepared Fe 2+ doped CsPbCl 3 NCs, which exhibited the highest PLQY of 6.2%. 35 Shyamal et al doped Fe 2+ in CsPbBr 3 NCs for use as an efficient photocatalyst for the reduction of CO 2 . 36 Singh et al reported Fe 3+ doped CsPbCl 3 , which improved the PLQY from 1.85% to 4.32%.…”
Section: Introductionmentioning
confidence: 99%